A Chain‐Elongated Oligophenylenevinylene Electrolyte Increases Microbial Membrane Stability. Issue 18 (25th March 2019) - Zhou, Cheng; Chia, Geraldine W. N.; Ho, James C. S.; Moreland, Alex S.; Seviour, Thomas; Liedberg, Bo; Parikh, Atul N.; Kjelleberg, Staffan; Hinks, Jamie; Bazan, Guillermo C.
Abstract: A novel conjugated oligoelectrolyte (COE) material, namedS6, is designed to have a lipid‐bilayer stabilizing topology afforded by an extended oligophenylenevinylene backbone.S6 intercalates biological membranes acting as a hydrophobic support for glycerophospholipid acyl chains. Indeed, Escherichia coli treated withS6 exhibits a twofold improvement in butanol tolerance, a relevant feature to achieve within the general context of modifying microorganisms used in biofuel production. Filamentous growth, a morphological stress response to butanol toxicity in E. coli, is observed in untreated cells after incubation with 0.9% butanol (v/v), but is mitigated byS6 treatment. Real‐time fluorescence imaging using giant unilamellar vesicles reveals the extent to whichS6 counters membrane instability. Moreover, S6 also reduces butanol‐induced lipopolysaccharide release from the outer membrane to further maintain cell integrity. These findings highlight a deliberate effort in the molecular design of a chain‐elongated COE to stabilize microbial membranes against environmental challenges. Abstract : A novel membrane‐intercalating phenylenevinylene oligoelectrolyte S6, comprising a long conjugated backbone, is designed, which can be used to attain a twofold improvement in the butanol tolerance of Escherichia coli . Biophysical experiments based on giant unilamellar vesicles indicate thatS6 counters membrane instability caused by butanol. This study demonstrates the power of materials design to achieve simple‐to‐apply methods that aid in inproving strategic properties of microbes.